Justification by Race: Wesley Swift’s White Supremacy and Anti-Semitic Theological Views in His Christian Identity Sermons - Ana Bochicchio (Gonzaga Library Publishing, 2021)
This article explores the discourses of Minister Wesley Albert Swift (1913–1970), one of the original and leading proponents of Christian Identity, a racial theology movement which emerged in the United States after World War II. It is not the aim of this study to analyze the discourse of Christian Identity as an isolated element, but to understand its interrelation with the political-religious culture of the country during the 1950s and 1960s. Christian Identity rhetoric may be understood based on its socio-historical context. During the formulative years of Christian Identity, nuclear anxieties, along with the fear of Communist infiltration, were deeply present within the white supremacist and their anti-Semitic views. At the same time, the civil rights movement of African Americans stimulated violent white supremacy politics and rhetoric by the extreme right. Combining the white hegemonic fear of minority advances in American society, Christian Identity was created as a cult for the racist right. As such, it attempted to legitimized white supremacy and perpetuate the Judeo-Communist Conspiracy myth. Race — as a biological issue that reflects the spiritual essence of a person — is the central element of anthropology built by Christian Identity, which claims the white race was literally created in the image of God. Therefore, they argue, it is the only race predestined for salvation. As an expression of an extreme Calvinist world view, Wesley Swift constructed a Christian theology that ideologically unified different political strategies of the postwar extreme right, which continues to this day.